DIGITAL LEARNING’S IMPACT: MEASURING THE EFFECTIVENESS OF ONLINE ENGLISH SPEAKING INSTRUCTION IN INDONESIA - Luruk, Yulita Lenitriana; Panggalih, Wahyun Bardianing; Muharlisiani, Lusy Tunik (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study investigates the effectiveness of an online English speaking instruction program in improving the speaking skills of adult learners in Indonesia. A total of 60 participants were divided into two groups: the experimental group (received ten weeks of online instruction) and the control group (received no intervention). The program employed a blended learning approach that included instructional videos, interactive exercises, and virtual speaking sessions with both native and non-native English-speaking instructors. Pre-tests and post-tests based on the IELTS speaking rubric were used to assess improvement. Results showed a significant increase in speaking scores in the experimental group, with an average gain of 1.5 points (from 5.2 to 6.7, p<0.01), while the control group showed no significant change (from 5.1 to 5.0). This study demonstrates that well-designed online learning can effectively enhance Indonesian students' English speaking skills, particularly in remote areas. Qualitative feedback highlights several strengths of the program, such as flexibility, convenience, and engaging content, although some participants experienced technical issues and internet connectivity problems. Therefore, online programs should include interactive elements and address technical challenges to optimize learning outcomes. Further research is recommended to explore various online teaching approaches and the impact of internet access disparities. Overall, digital learning is seen as an effective and scalable alternative for English education in Indonesia. ABSTRACT Studi ini meneliti efektivitas program pembelajaran berbicara bahasa Inggris secara daring dalam meningkatkan keterampilan berbicara peserta didik dewasa di Indonesia. Sebanyak 60 peserta dibagi menjadi dua kelompok: kelompok eksperimen (menerima pembelajaran daring selama sepuluh minggu) dan kelompok kontrol (tidak menerima intervensi). Program ini menggunakan pendekatan pembelajaran campuran yang mencakup video pembelajaran, latihan interaktif, dan sesi berbicara virtual dengan instruktur penutur asli dan non-penutur asli bahasa Inggris. Tes awal dan tes akhir berdasarkan rubrik IELTS speaking digunakan untuk menilai peningkatan kemampuan. Hasil menunjukkan peningkatan skor berbicara yang signifikan pada kelompok eksperimen, dengan rata-rata peningkatan sebesar 1,5 poin (dari 5,2 menjadi 6,7, p<0,01), sementara kelompok kontrol tidak menunjukkan perubahan signifikan (dari 5,1 menjadi 5,0). Penelitian ini menunjukkan bahwa pembelajaran daring yang dirancang dengan baik dapat secara efektif meningkatkan kemampuan berbicara bahasa Inggris peserta didik di Indonesia, terutama di daerah terpencil. Umpan balik kualitatif mengungkap kelebihan program ini, seperti fleksibilitas, kenyamanan, dan materi yang menarik, meskipun beberapa peserta menghadapi kendala teknis dan masalah koneksi internet. Oleh karena itu, program daring sebaiknya mencakup elemen interaktif dan solusi atas kendala teknis untuk memaksimalkan hasil belajar. Studi lanjutan disarankan untuk mengeksplorasi berbagai pendekatan pengajaran daring dan dampak perbedaan akses internet. Secara keseluruhan, pembelajaran digital dipandang sebagai alternatif yang efektif dan skalabel untuk pendidikan bahasa Inggris di Indonesia.